Disease burden associated with alpha-1 antitrypsin deficiency: systematic and structured literature reviews. (23rd March 2022) - Miravitlles, Marc; Herepath, Mike; Priyendu, Asim; Sharma, Sheetal; Vilchez, Tatiana; Vit, Oliver; Haensel, Michaela; Lepage, Virginie; Gens, Helena; Greulich, Timm
Alpha-1 antitrypsin deficiency (AATD) is a rare genetic disorder characterised by reduced levels of circulating alpha-1 antitrypsin and an increased risk of lung and liver disease. Recent reviews of AATD have focused on diagnosis, epidemiology and clinical management; comprehensive reviews examining disease burden are lacking. Therefore, we conducted literature reviews to investigate the AATD disease burden for patients, caregivers and healthcare systems. Embase, PubMed and Cochrane libraries were searched for AATD publications from database inception to June 2021, in accordance with Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines. Most published AATD studies were small and short in duration, with variations in populations, designs, measures and outcomes, complicating cross-study comparisons. AATD was associated with significant pulmonary and hepatic morbidity. COPD, emphysema and bronchiectasis were common lung morbidities, where smoking was a key risk factor. Fibrosis and steatosis were the most common liver complications reported in patients with a PiZ allele. Health status analyses suggested a poorer quality of life for AATD patients diagnosed with COPD versus those with non-AATD-associated COPD. The burden for caregivers included loss of personal time due to caring responsibilities, stress and anxiety. AATD was also associated with high direct medical costs and healthcare resource utilisation. AATD is a rare genetic disorder associated with a considerable burden of lung and liver disease and high healthcare resource utilisation. However, available data are scarce and further research is needed to better understand the burden of this disease. https://bit.ly/3IWtQQ1